Wanita dan Dakwah: Gerakan Dakwah Keputrian UKMI Ar-Royyan UNRI - Amalia Mutiara Pratiwi; Pipir Romadi; Muhammad Irham (LPPM STISIP Persada Bunda, 2023)
This article presents the results of research women and da'wah on the Keputrian UKMI Ar-Royyan at UNRI. This study aims to describe the role of women and the da'wah movement carried out by the Keputrian UKMI Ar-Royyan. This research was conducted with a descriptive qualitative approach. Data was collected by means of observation, interviews and documentation. The results of this study indicate that: First, the role of Muslim women of UKMI Ar-Royyan in preaching is adjusted to the vision and mission they have so that the goals to be achieved. Second, the form and movement of da'wah in the UKMI Ar-Royyan Keputrian there are three bureaus, namely the Muslimah development, female circle bureau, and Muslimah syiar bureau. Third, the obstacles in preaching and how to maintain ukhuwah obstacles that usually occur in the form of differences in perception or differences of opinion as for how to maintain ukhuwah by holding MABIT agendas and meet ups or meetings to strengthen ukhuwah between one Muslim woman with another.